The differential Europeanisation of Central and Eastern Europe, 1989-2000: a constructivist study of the foreign policy identities of Poland, Bulgaria and Russia - Filipova, RV (2018)
The thesis addresses the puzzle of the differential integration of former communist states in the Euro-Atlantic community of nations between 1989 and 2000. Notwithstanding the predominant universalist-rationalist assumption that the adoption of an institutional-administrative blueprint for reform could lead to convergence between East and West, countries such as Poland, Bulgaria and Russia did not converge similarly (or at all) on the West European normative model and framework of international relations. To account for this divergence, the thesis examines the impact of the culturally-historically informed, Polish, Bulgarian and Russian identities and conceptions of 'Europe' (as opposed to the formal-institutional transition from one system to another) on the process of foreign policy transformation. The doctoral research employs Constructivism, Social Psychological insights and an interpretivist methodology, drawing on 75 elite interviews. The main argument states that differential Europeanisation can be understood on the basis of differentiated levels of inclusion and establishment of relations of mutual recognition and belongingness – ¬substantiated by a differentiated extent of ideational affinity (i.e., normative compatibility), which are (re)enacted in the interactive, mutually constitutive process of identification between Self and Other (i.e., between Poland, Bulgaria and Russia and (Western) Europe). Three propositions of 'thick', 'ambivalent' and 'thin' Europeanisation are derived from the argument (whereby the comparative benchmark of Europeanisation is an ideal-typical model of European-ness). Key contributions focus on the development of a refined Constructivist theory and a systematic empirical comparison of Polish, Bulgarian and Russian foreign policy identities. Also, the study’s conclusions reinvigorate and reconfirm the importance of the continuity (rather than just constant flux) of culturally-historically shaped patterns of group self-understandings and sub-regional identifications as well as Constructivism’s greater plausibility in accounting for the research puzzle than (Neoclassical) Realism through the stipulation of a mutually constitutive relationship between international and domestic factors and between ideational and interest-based considerations.